Reduced urine volume and changed renal sphingolipid metabolism in P2ry14-deficient mice - Baalmann, Fabian; Brendler, Jana; Butthof, Anne; Popkova, Yulia; Engel, Kathrin M.; Schiller, Jürgen; Winter, Karsten; Lede, Vera; Ricken, Albert; Schöneberg, Torsten; Schulz, Angela (Frontiers in Cell and Developmental Biology, 2023)
The UDP-glucose receptor P2RY14, a rhodopsin-like G protein-coupled receptor (GPCR), is abundantly expressed in mouse renal collecting duct principal cells and epithelial cells surrounding the renal papilla tip. To better understand its physiological function in kidney, we took advantage of a P2ry14 reporter and gene-deficient (KO) mouse strain. Morphometric studies showed an impact of the receptor function on the structure of the kidney. KO mice had a broader cortex relative to the total kidney area than wild-type (WT) mice. In contrast, the area of the outer stripe of the outer medulla was larger in WT compared to KO mice. Transcriptome comparison of the papilla region of WT and KO mice revealed differences in gene expression of extracellular matrix proteins (e.g., decorin, fibulin-1, fibulin-7) and proteins involved in sphingolipid metabolism (e.g., small subunit b of the serine palmitoyltransferase) and other related GPCRs (e.g., GPR171). Using mass spectrometry changes in the composition of sphingolipid species leading to longer chain lengths were detected in the renal papilla. At the functional level, we found that KO mice have a reduced urine volume but an unchanged glomerular filtration rate under normal chow and salt diets. Our study revealed P2RY14 as a functionally important GPCR in collecting duct principal cells and papilla epithelial cells and the possible involvement of P2ry14 in nephroprotection by regulation of decorin.